Ambient air pollution exposures and risk of drug-resistant tuberculosis. (March 2019) - Yao, Liu; LiangLiang, Cui; JinYue, Liu; WanMei, Song; Lili, Su; YiFan, Li; HuaiChen, Li
Abstract: Background: Few epidemiological studies have explored the effects of air pollution on the risk of drug-resistant tuberculosis (DR-TB). Objective: To investigate the short and long term residential concentrations of ambient air pollutants (particulate matter <10 μm in diameter (PM10 ) and particulate matter≤2.5 μm in diameter (PM2.5 ), nitrogen dioxide (NO2 ), sulfur dioxide (SO2 ), ozone (O3 ), and carbon monoxide (CO)) in relation to the risk of DR-TB in a typical air pollution city, Jinan city, China. Methods: A total of 752 new culture-confirmed TB cases reported in TB prevention and control institutions of Jinan from January 1, 2014 to December 31, 2015 were included. Average individual-level concentrations of air pollution for 5 different exposure windows, vary from 90 days to 720 days to diagnosis were estimated using measurements from monitor closest to the patient home addresses. Logistic regression model adjusted for potential confounders was employed to evaluate correlation between air pollution and DR-TB risk at different five exposure windows individually. Results: There were substantially increased mono-drug resistance and poly-drug resistance risks for ambient PM2.5, PM10, O3, and CO exposures. High exposure to PM2.5, PM10, and CO was also significantly associated with increased incidence of multi-drug resistance (MDR) both in the single- and multi-pollutants regression models. The dominant positive associations for PM2.5 was observed at 540 days exposure, for O3 was observed at 180 days exposure, and for PM10 and CO was observed from 90 days to 540 days exposures. Conclusions: Our finding suggest that exposure to ambient air pollution (PM2.5, PM10, O3, and CO) are associated with increased risk of DR-TB. We provided epidemiological evidence of association between pollution exposure and mono-, poly- and multi-drug resistance. Highlights: To investigate the association of residential concentrations of air pollutants and the risk of drug resistant (DR) TB. There were substantially increased mono- and poly-DR TB risks for ambient PM2.5, PM10, O3, and CO exposures. High exposure to PM2.5, PM10, and CO was also significantly associated with increased risk of MDR. The positive effect for PM10 and CO was observed from 90 days to 540 days exposure.